Viability and resilience of small-scale fisheries through cooperative arrangements - Hardy, Pierre-Yves; Béné, Christophe; Doyen, Luc; Pereau, J.C.; Mills, D. (Cambridge University Press, 2016)
The small-scale fisheries sector in many Pacific islands is facing increasing challenges in relation to resource availability, economic opportunity, and demographic and social pressure. In particular, intensifying cash-oriented livelihood strategies can exacerbate existing vulnerabilities and threaten food security and resource conservation. In this paper the authors develop a bio-economic model and a quantitative measure of resilience in order to explore the interaction between socio-economic and ecological dynamics, and to analyze the potential role that cooperation and collective arrangements can play in this interaction to maintain the viability of the system. Based on the case of the system known as wantok typically found in the Solomon Islands, numerical examples are used to explore the potential gain that cooperation between fishers can bring in terms of subsistence, profitability and ecological performances, as well as the resilience of the whole system to shocks.